The true meaning of dreams - Gewargis, Youash Arkhiom (International Journal of Dream Research, 2016)
Dream researchers have failed to solve the dream’s riddle. The main reason is that almost all have adopted the content-approach, initiated by the two prominent pioneers, Sigmund Freud and Carl Jung. In this study dreams will be viewed from an entirely different vantage point: Dreams are seen as a component of a more intricate mechanism, run by the brainstem and in collaboration with the peripheral nervous system’s two parts, namely the parasympathetic and sympathetic nervous systems; the vision; pontes and a few muscles. This complex mechanism takes over the task of safeguarding the living organisms (mostly viviparous mammals and birds) during the sleep—a physiologically dictated slumber that all living organisms must undergo, to regenerate and rejuvenate. At sleep, the body functions are lowered to the minimum permissible level of their respective operations, and sustained at such a dangerous level, without allowing the body from slipping into the impermissible and undesirable territories; thence obtaining the best regeneration and rejuvenation results for the perpetually operating body organs, like central brain and the heart, prior to the start of a new cycle of normal duties. In this study, the role of each component of this complex defence-mechanism will be thoroughly explained; and how together they safeguard the organism from two main risks within, that surface out mostly during the deep- sleep level.